Tantangan Dan Transformasi: Membangun Profesionalisme Guru Geografi Di Era Digital Untuk Pendidikan Unggul - Masruroh Masruroh; Sunarty Eraku; Moch Rio Pambudi (Postgraduate, University of Mataram, 2024)
Education is the pillar and foundation of nation building and in the digital era that must develop rapidly, technology integration is a must. In an era filled with advanes in digital technology, new challenges have emerged in the world of education, especially in building professionalism for educators. This research aims to identify challenges and transformation efforts in building the professionalism of geography teachers in the digital era in the five best schools in Gorontalo City. This study uses a qualitative approach with an in-depth interview method with 10 geography teachers from each school. Data will be collected through learning observations, interviews with geography teachers, and document analysis. Teaching patterns, important findings, and emerging trends in the digital era related to challenges and changes in building the professionalism of geography teachers in the digital era will be analyzed thematically. The results show that despite significant challenges, such as limited technological infrastructure and resistance to change, teachers are actively trying to integrate digital technology in learning. This transformation is seen in the use of Geographic Information Systems (GIS) and digital project-based learning that have improved student engagement and learning effectiveness. These findings highlight the importance of institutional support and continuous professional development to strengthen teacher professionalism in the digital era.